FAKTOR - FAKTOR YANG MEMPENGARUHI KEJADIAN KEPUTIHAN DITINJAU DARI KEBIASAAN VULVA HYGIENE PADA IBU PETANI DI DESA NGANCAR KECAMATAN GIRIWOYO KABUPATEN WONOGIRI - Trisnowati, Tatik; Solikah, Siti Nur (Jurnal AKPER GSH, 2018)
Background In Ngancar Village, Giriwoyo has a population of different ages, levels of education, and different economic and occupational status. Ngancar Village, Giriwoyo is divided into 8 (eight) dukuh. When conducted preliminary study with question and answer between researchers with mothers of farmers of 50 mothers, 20 of them experienced abnormal vaginal discharge and never did the treatment of his feminine area.The purpose To know factors which influence deceived events from hygiene vulva habits on farmers 'mothers in ngancar village giriwoyo district, Wonogiri district.The subjects The population of farming mothers in Ngancar village, Giriwoyo is 200 people. Sampling technique used in this research is Purposive Sampling and sample of 50 farmer mothers.Methods This research type of descriptive research with design that used for this research is cross sectional that is research conducted one time observation only. Population in this research is all farmer mother in Ngancar village, Giriwoyo. It was found that most of respondent factor factors influencing vulva hygiene with incidence of leucorrhea at the mother of farmer in village ngancar have bigger influence to the respondent earning <Rp 500.000 per month counted 30 person or 60%, while the respondent earning <Rp 500.000 and ≥ Rp 1,000 As many as 5 people or 10%. Based on age level most respondents aged 46 - 50 years are 35 or 70%, while respondents aged <45 years as many as 5 people or 10%, while respondents aged> 51 years as many as 10 people or 20%. Based on education 60% or 30 people with elementary education, 15 people or 30% of junior high school, 5 people or 10% high school and based on 40% knowledge level.The conclusion It can be concluded that factors affecting the vulva hygiene with the incidence of leucorrhea in the mother of farmers in Ngancar, Giriwoyo, Wonogiri regency in 2017 ie economic factors per month <Rp 500,000 of 60%., Age factor at the age of 46-50 years of 70%, Factor education in elementary education by 60%. Knowledge factor at knowledge level is big enough 40%.